The Degree of the National Peculiarity in the Zoonomic Components in the Uzbek and English Phraseology - Kosimova Shokhida Shokir qizi (Researchparks Publishing, 2022)
This article is based on the modern compressional analyses which conducted some national peculiarities of Uzbek and English phraseological units. As a result of the research that is figured out the role of animals in human life has always been extremely high, especially when humanity emerged, when humans and animals lived together in a natural environment.